Hypersurface Family with a Common Isoasymptotic Curve. (31st December 2014) - Bayram, Ergin; Kasap, Emin
Abstract : We handle the problem of finding a hypersurface family from a given asymptotic curve in R 4 . Using the Frenet frame of the given asymptotic curve, we express the hypersurface as a linear combination of this frame and analyze the necessary and sufficient conditions for that curve to be asymptotic. We illustrate this method by presenting some examples.